Currículos da educação básica do Peru e Brasil: prescritos e praticados - Athias, Miguel Fortunato (2015)
This research aims to understand the importance of challenging issues related to curriculum development and teacher training in mathematics education area. Conducts comparative study of curriculum proposals for federal, published by government institutions in Peru and Brazil, and also interviews with teachers and principals levels of regular basic education, to understand the prescribed curriculum and practiced in these countries. Currently this thesis forms part of the research group "Math teacher: Training, Job, Knowledge and Teaching Work." But before formed part of the group "Development Research Curriculum in Mathematics and teacher education." Dedicated to the organization and curriculum development and project "Comparative research on organization and curriculum development in Mathematics Education area of the Latin American countries" has articles that connect ideas from two research groups. I sought rapprochement with the Antônio Nóvoa ideas, Maria A. Civatta Franco, Manoel B . Lourenço Filho and Elma J G de Carvalho for understanding the Comparative Study; of Feran Ferrer to structure the comparative research; J. Gimeno Sacristan, Luis Rico Romero, William E. Doll Jr., Marcio Antonio da Silva and Alan Bishop, for understanding curriculum and in particular facing Mathematics;. and George Polya, to design problem solving In pursuit of the objective of the research, the main comparative result of the documentary of points similarity in views on use the Troubleshooting as axle and strategy in the teaching and learning of mathematics. Already in interviews with teachers and principals in both countries, concluded that the Peruvian actors have better working relationship in Mathematics in Basic Education with the official curriculum in primary and secondary levels, than the actors in Brazil. The influence of national and state assessments in the performance of Brazil's teachers is one of the differences, as well as the monitoring of the student by the same teacher in Peru to enter the primary or secondary. These findings might be explained by the fact that in Brazil there are no mandatory curriculum proposals, whether at the local, state or national, which does not happen in Peru, where the curricula guide the process